Toward a Glutamate Hypothesis of Frontotemporal Dementia - Benussi, Alberto; Alberici, Antonella; Buratti, Emanuele; Ghidoni, Roberta; Gardoni, Fabrizio; Di Luca, Monica; Padovani, Alessandro; Borroni, Barbara (Frontiers in Neuroscience, 2019)
Frontotemporal dementia (FTD) is a heterogenous neurodegenerative disorder characterized by the accumulation of Tau and TDP-43 inclusions. Emerging evidence has shown that FTD is characterized by a series of changes in several neurotransmitter systems, including serotonin, dopamine, GABA and, above all, glutamate. Indeed, several studies have now provided preclinical and clinical evidence that glutamate is key in the pathogenesis of FTD. Animal models of FTD have shown a selective hypofunction in NMDA and AMPA receptors, while in patients, glutamatergic pyramidal neurons are depleted in several areas, including the frontal and temporal cortices. Recently, a selective involvement of the AMPA GluA3 subunit has been observed in patients with autoimmune anti-GluA3 antibodies, which accounted for nearly 25% of FTD patients, leading to a decrease of the GluA3 subunit synaptic localization of the AMPA receptor and loss of dendritic spines. Other in vivo evidence of the involvement of the glutamatergic system in FTD derives from non-invasive brain stimulation studies using transcranial magnetic stimulation, in which specific stimulation protocols have indirectly identified a selective and prominent impairment in glutamatergic circuits in patients with both sporadic and genetic FTD. In view of limited disease modifying therapies to slow or revert disease progression in FTD, an important approach could consist in targeting the neurotransmitter deficits, similarly to what has been achieved in Parkinson’s disease with dopaminergic therapy or Alzheimer’s disease with cholinergic therapy. In this review, we summarize the current evidence concerning the involvement of the glutamatergic system in FTD, suggesting the development of new therapeutic strategies.